2021
DOI: 10.3389/fpsyg.2021.694297
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Assistive Technologies and Robotics in Long-Term Care Facilities: A Three-Stage Assessment Based on Acceptance, Ethics, and Emotions

Abstract: Assistive technologies including assistive robots (AT/AR) appear to be a promising response to the increasing prevalence of older adults in need of care. An increasing number of long-term care facilities (LTCFs) try to implement AT/AR in order to create a stimulating environment for aging well and to reduce workload for professional care staff. The implementation of new technologies in an organization may lead to noticeable cultural changes in terms of social interactions and care practices associated with pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Dyb et al [ 8 ] suggested a more in-depth exploration of staff’s visions would facilitate technology planning and implementation. Franke et al [ 9 ] stated the importance of exploring the role of leadership in technology implementation. Having frontline staff to facilitate quality improvement with a lack of training and support from the management level was associated with the failure of the change process [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dyb et al [ 8 ] suggested a more in-depth exploration of staff’s visions would facilitate technology planning and implementation. Franke et al [ 9 ] stated the importance of exploring the role of leadership in technology implementation. Having frontline staff to facilitate quality improvement with a lack of training and support from the management level was associated with the failure of the change process [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential loss of jobs in certain sectors requires careful consideration of workforce transition strategies, including upskilling and reskilling initiatives. Ethical deployment of robotics involves a commitment to supporting affected workers through periods of transition (Franke et al, 2021) [23] . Ensuring the safety of human workers collaborating with robots is paramount.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…To facilitate successful implementation and integration of technological innovation in a complex healthcare environment, factors of multiple levels (e.g., patients, organizational, and policy levels) need to be considered systematically (8). Some factors affecting the implementation of evidence-based practices like safety, social justice, usefulness and appropriateness, and user impact were studied (9). However, there are factors of implementation that have not been fully explored, e.g., perspectives of frontline staff and leaders (6).…”
Section: Needs To Explore Factors For Successful Implementationmentioning
confidence: 99%
“…Dyb et al (10) suggested that a more in-depth exploration of staff's visions would facilitate technology planning and implementation. Franke et al (9) stated the importance of exploring the role of leadership in technology implementation. Having frontline staff to facilitate quality improvement with a lack of training and support from the management level was associated with the failure of the change process (6).…”
Section: Needs To Explore Factors For Successful Implementationmentioning
confidence: 99%